Engine performance and emissions analysis using “Envo Diesel” and coconut biodiesel blended fuel as alternative fuels - Liaquat, A.M.; Kalam, M.A.; Masjuki, Haji Hassan; Jayed, M.H. (2011)
The Environmental concerns and regulations to reduce green house gas emission and fluctuation of fossil fuel price have stimulated research on alternative fuels. Moreover, use of unproductive land to produce vegetable oil which is a potential biodiesel source has opened up a way to reduce oil bill. Biodiesel does not need major modification in engine, even though it causes some engine problems in long term use. This paper presents experimental results that evaluates the performance and exhaust emissions of a diesel engine operated on “Envo Diesel” which consists of 5% palm diesel and 95% ordinary diesel fuel (also termed as P5) and C5 (5% coconut biodiesel and 95% ordinary diesel fuel. Experimental results showed that P5 and C5 reduced brake power compared to diesel fuel by 1.2% and 0.7% respectively. Emissions such as HC, smoke, CO and NOx concentration were lesser for P5 and C5. The results of this investigation will be used to partial replacement of diesel fuel using low percentage of methyl ester (maximum 5%) obtained from waste vegetable oils.